The Gramsci and Arrighi influence to the understanding of international hegemony - Todescato, Dorival Bruno Leal (2019)
The present article aims to expose the influence of Antônio Gramsci on Giovanni Arrighi 's thinking about the concept of international hegemony. The motivation in studying Arrighi resides in the theoretical peculiarity of the author, who is not necessarily a Marxist, but part of the historical premise when analyzing capitalism at the international level. Therefore our work was divided into three parts: a) we tried to show what Gramsci understood by hegemony, that is, his conception of hegemony still on national bases; b) illustrate how Gramsci worked on ideas that help to understand hegemony in international relations; c) to show how Arrighi adopted the concept of hegemony worked by Gramsci in his own interpretation of international relations in historical capitalism. Recebido: 29/01/2019Aceito: 13/05/2019